Effect of Health Service Quality Education on Phlebitis Prevention Practices among Nurses in Community Health Centers: A Quasi-Experimental Study - Andi Mappanganro; Andi Tenri Abeng (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Phlebitis is one of the most common complications associated with intravenous (IV) catheter insertion and is characterized by inflammation of the vein wall, causing pain, redness, and discomfort. This study aimed to analyze the effect of health service quality education on phlebitis prevention practices among healthcare workers at selected inpatient Community Health Centers (Puskesmas) in Makassar City. This study employed a quasi-experimental design using a one-group pretest-posttest approach. The study was conducted from January to March 2025 at Bara-Baraya Community Health Center, Mamajang Kassi-Kassi Community Health Center, and Pattingalloang Community Health Center in Makassar City. A total of 50 healthcare workers were selected using purposive sampling based on predetermined inclusion criteria. Data were collected using validated questionnaires and observation sheets before and after the educational intervention. Instrument validity and reliability tests were conducted prior to data collection, and all instruments were declared valid and reliable. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed that 37 respondents experienced an increase in posttest scores, while 13 respondents showed no change. No respondents experienced a decrease in scores after the intervention. The Wilcoxon Signed Rank Test showed a significant difference between pretest and posttest scores with a p-value of 0.000 (p < 0.05). These findings indicate that health service quality education had a significant effect on improving phlebitis prevention practices among healthcare workers at Community Health Centers in Makassar City.